A Series Circuit of Thermal Rectifiers: An Effective Way to Enhance Rectification Ratio. Issue 6 (1st December 2016) - Hu, Shiqian; An, Meng; Yang, Nuo; Li, Baowen
Abstract : A novel approach is proposed to enhance the thermal rectification ratio, namely, arranging two thermal rectifiers in series. Through theoretical analysis and molecular dynamics simulations on graphene/phononic crystal structures, the results show that the series thermal rectifiers enhance thermal rectification ratio significantly, compared to a single rectifier. Meanwhile, the results of theoretical prediction match well with simulation results.